2009
DOI: 10.1128/ec.00135-09
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Chromosome Transfer, a Mechanism for the Evolution and Differentiation of a Plant-Pathogenic Fungus

Abstract: pathotype strains, were compared to those of tomato pathotype strains collected worldwide. This revealed that the sequences of both CDC genes were identical among five A. alternata tomato pathotype strains having different geographical origins. On the other hand, the sequences of other genes located on chromosomes other than the CDC are not identical in each strain, indicating that the origin of the CDC might be different from that of other chromosomes in the tomato pathotype. Telomere fingerprinting and restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 48 publications
(68 reference statements)
3
106
1
1
Order By: Relevance
“…Host-selective toxin biosynthetic genes of A. alternata pathotypes appeared to be clustered on small chromosomes of Ͻ2.0 Mb in most of the strains tested (2,3,13,15,20,21,33,35). We demonstrated that small chromosomes that contain toxin biosynthetic genes from the strawberry, apple, and tomato pathotypes are conditionally dispensable (CD) chromosomes (2,15,21).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Host-selective toxin biosynthetic genes of A. alternata pathotypes appeared to be clustered on small chromosomes of Ͻ2.0 Mb in most of the strains tested (2,3,13,15,20,21,33,35). We demonstrated that small chromosomes that contain toxin biosynthetic genes from the strawberry, apple, and tomato pathotypes are conditionally dispensable (CD) chromosomes (2,15,21).…”
Section: Discussionmentioning
confidence: 94%
“…We demonstrated that small chromosomes that contain toxin biosynthetic genes from the strawberry, apple, and tomato pathotypes are conditionally dispensable (CD) chromosomes (2,15,21). We are now focusing on the structural and functional analysis of the 1.05-Mb CD chromosome that contains the AFT genes of the strawberry pathotype to identify the entire gene cluster and to understand the evolution of toxin biosynthesis and the origin of CD chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those discussed earlier, examples include the ETP and fumonisin clusters between ascomycetes, 34,39 penicillin between bacteria and fungi, 42 and genes involved in host-specific toxin production and host specificity between Alternaria pathotypes or species. 43,44 The increasing availability of fungal genome sequences should allow testing of alternative hypotheses.…”
Section: Similar Mechanisms Occur In Other Secondary Metabolism Genementioning
confidence: 99%
“…The transfer of whole chromosomes was also involved in the acquirement of pathogenicity by the tomato pathogens Alternaria alternata and Fusarium oxysporum f. sp. lycopersici (Akagi et al 2009;Ma et al 2010). Finally, Richards et al (2011) showed how interkingdom gene transfer from filamentous fungi to oomycetes of at least 21 genes with roles in nutrient acquisition, degradation of plant surface components, and suppression of plant defences led to the appearance of plant pathogenic oomycetes.…”
Section: Introductionmentioning
confidence: 99%